The fall of the Roman Empire - Nardo, Don, 1947- (San Diego, Calif. : Greenhaven Press, 1998)
Discusses some of the causes that may have led to the end of the Roman Empire, including changes in population, economic decay, class and religious divisions, and military conquest.
Includes bibliographical references (p. [131]-139) and index.
Keywords: Rome (Italy) -- History -- Empire, 284-476 -- Juvenile literature; Rome (Italy) -- History -- Empire, 284-476.